Praying into the Void: Curative Eschatology, Crip Ancestry, and Disability Justice - Lazarus, Kevin (Journal of the Society of Christian Ethics, 2025)
Traditional Christian notions of salvation, healing, and redemption are often structured by a curative theological imaginary that precludes disability from our collective pasts and futures. To resist the eschatological erasure of disability, some disability theologians have called for radical attention to the present—to disabled people, here and now—as the primary site of the Spirit’s activity. Departing from a strict theological presentism, this essay seeks to imagine redemption apart from curative logics without dismissing all desires for bodily change. Interpreting the archival research practices of disabled activist-writers through the lens of crip ancestry, I develop a negative theological hermeneutic in which the search for crip ancestors in the Christian tradition exposes the violence that erases disabled lives, cultivating a longing for a future where disabled people are not lost to history.